O papel do grupo no processo de significação de licenciandos e professores da educação básica sobre a organização do ensino de Matemática na perspectiva lógico-histórica - Leandro, Everaldo Gomes (Universidade Federal de São Carlos, 2017)
In this research, we aim to understand the role of a group of studies and research in the process of signification of Math students and teachers of basic education with regard to the organization of teaching mathematics in the logical-historical perspective. Specifically we seek to (1) Understand the meaning process, indicating the senses and meanings attributed by the subjects of a group of studies and researches to the organization of the teaching of Mathematics in the logical-historical perspective and; (2) Evidence of elements that can contribute to the discussion about the organization of mathematics teaching in the logic-historical perspective. This research is qualitative and was constituted in a case study developed from the historical-cultural theory. The research instruments consisted of recordings of the study group meetings and dialogical interviews with the coordinator and participants. Based on the interpretive analysis of the data, focusing on the senses and meanings attributed by the subjects, it was possible to perceive that the diversity of participants contributes to the collective discussions about the elements that make up the teaching organization, such as: Interface between Mathematics and teaching, the triggering situations of learning or the role of reading and writing of the students and teachers for such organization, and that the group, in turn, assumes a central role in the training of the members with regard to related contributions: The writing of its participants, the understanding of texts and the creation of triggering situations of learning of Mathematics. From the senses and meanings expressed on the role of the History of Mathematics in the organization of teaching it was possible to analyze the need to study, in a collective way, History in Marx's thought, the History of Mathematics in its interrelationship with Philosophy and the role of Philosophy as part of the organization of Mathematics teaching. We can also perceive, through the process of meaning of the subjects, the role of the instruments in the organization of teaching and the role that the community assumes to think, elaborate and evaluate such instruments. The results reveal that the first contact of the subjects, specifically of the undergraduate students, with the logical-historical perspective and the organization of the teaching of Mathematics in this perspective occurs through the participation of the subjects in study groups and researches. On the other hand, we could see that the constitution of collective spaces of discussion about the organization of mathematics teaching contributes to overcoming the individual competence of the subjects and helps to think the formation of teachers and future teachers as a shared activity.
The role of the group in the process of signifying undergraduate students and teachers of basic education on the organization of mathematics teaching in the logical-historical perspective
Keywords: Educação matemática histórico-cultural; Organização do ensino de Matemática; Grupos de estudos; Historical-cultural mathematics education; Organization of Mathematics teaching; Study groups; CIENCIAS HUMANAS::EDUCACAO